Trends and management implications of human‐influenced life‐history changes in marine ectotherms. Issue 4 (9th March 2016) - Audzijonyte, Asta; Fulton, Elizabeth; Haddon, Malcolm; Helidoniotis, Fay; Hobday, Alistair J; Kuparinen, Anna; Morrongiello, John; Smith, Anthony DM; Upston, Judy; Waples, Robin S
Abstract: Evidence is accumulating that many marine ectotherms are undergoing rapid changes in their life‐history characteristics. These changes have been variously attributed to fisheries‐induced evolution, inhibited adult growth rate due to oxygen limitation at higher temperatures, and plastic responses to density dependence or changes in ocean productivity. Here, we review the diverse underlying mechanisms by which plastic and evolutionary responses to climate change and fisheries are likely to produce similar life‐history trends in harvested marine ectotherms, leading to faster life‐histories with earlier maturation and smaller adult size‐at‐age. While mechanistically understanding these growth and maturation changes may be difficult, it is becoming clear that changing life‐histories will lead to modified population dynamics, productivity and natural mortality of the affected species. We discuss how the observed and expected life‐history changes could affect the assumptions and uncertainty within single and multispecies models currently used in marine ecosystem management, highlighting that models which allow for dynamic life‐history traits often report significantly different estimates of stock biomass. Given that both climate‐ and harvest‐induced life‐history changes are likely to intensify and possibly amplify each other, there is an urgent need to adequately assess the implications of faster life‐histories for marine ecosystem management. This is especially true for data‐poor stocks, where growth and maturation are not regularly assessed. Targeted monitoring can be used to inform responsive management, but for improved sustainability outcomes, a precautionary approach to management that is robust to life‐history trends is advised.